Nanoparticle transport in epithelial cells: pathway switching through bioconjugation - Fowler, Robyn; Vllasaliu, Driton; Trillo, Francisco Fernández; Garnett, Martin; Alexander, Cameron; Horsley, Helen; Smith, Bryan; Whitcombe, Ian; Eaton, Mike; Stolnik, Snow (Wiley-VCH Verlag, 2013)
The understanding and control of nanoparticle transport into and through cellular compartments is central to biomedical applications of nanotechnology. Here, it is shown that the transport pathway of 50 nm polystyrene nanoparticles decorated with vitamin B12 in epithelial cells is different compared to both soluble B12 ligand and unmodified nanoparticles, and this is not attributable to B12 recognition alone. Importantly, the study indicates that vitamin B12-conjugated nanoparticles circumnavigate the lysosomal compartment, the destination of soluble vitamin B12 ligand. Whereas cellular trafficking of soluble B12 is confirmed to occur via the clathrin-mediated pathway, transport of B12-conjugated nanoparticles appears to predominantly take place by a route that is perturbed by caveolae-specific inhibitors. This data suggests that, following its conjugation to nanoparticles, in addition to dramatically increasing the cellular uptake of nanoparticles, the normal cell trafficking of B12 is switched to an alternative pathway, omitting the lysosomal stage: a result with important implications for oral delivery of nanoparticulate diagnostics and therapeutics.